1985
DOI: 10.1029/jd090id06p10719
|View full text |Cite
|
Sign up to set email alerts
|

Identification of 18O‐isotopic lines of ozone in infrared ground‐based solar absorption spectra

Abstract: A number of relatively well‐isolated lines of the v3 bands of 16O18O16O and 16O16O18O have been identified in high‐resolution solar absorption spectra recorded with the Fourier transform interferometer at the National Solar Observatory on Kitt Peak (elevation 2095 m, latitude 31.9°N). Based on spectroscopic parameters derived from ozone laboratory spectra recorded with the same instrument, the heavy ozone content of the total column of ozone has been determined from measurements of the equivalent widths of 16O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
2

Year Published

1986
1986
2016
2016

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 59 publications
(16 citation statements)
references
References 21 publications
0
14
2
Order By: Relevance
“…Since the discovery over 30 years ago, these findings have been confirmed by further mass spectrometer measurements of atmospheric samples (Krankowsky et al, 2007), and by high-resolution spectroscopy using surface-based total-column measurements (Rinsland et al, 1985;Meier and Notholt, 1996), balloon-borne instruments (Abbas et al, 1987;Goldman et al, 1989;Johnson et al, 2000;Haverd et al, 2005), and space-based spectrometers (Irion et al, 1996;Piccolo et al, 2009;Sato et al, 2014). Laboratory research indicated that the observed isotopic enrichment is primarily controlled by unusually strong isotope effects associated with the O 3 formation reaction (Morton et al, 1990):…”
Section: Introductionmentioning
confidence: 63%
“…Since the discovery over 30 years ago, these findings have been confirmed by further mass spectrometer measurements of atmospheric samples (Krankowsky et al, 2007), and by high-resolution spectroscopy using surface-based total-column measurements (Rinsland et al, 1985;Meier and Notholt, 1996), balloon-borne instruments (Abbas et al, 1987;Goldman et al, 1989;Johnson et al, 2000;Haverd et al, 2005), and space-based spectrometers (Irion et al, 1996;Piccolo et al, 2009;Sato et al, 2014). Laboratory research indicated that the observed isotopic enrichment is primarily controlled by unusually strong isotope effects associated with the O 3 formation reaction (Morton et al, 1990):…”
Section: Introductionmentioning
confidence: 63%
“…The first experimental evidence that the heavy isotope of ozone at mass 50 is enriched above statistically expected values was presented by Mauersberger [1981] from an analysis of in situ mass spectrometer measurements. Additional measurements using both optical instrumentation and mass spectrometers have verified the large enrichment of 5øO 3 which varies in magnitude from 10 to 45% [Rinsland et al, 1985;Abbas et al, 1987;Goldman et al, 1989].…”
Section: Introductionmentioning
confidence: 99%
“…Subsequent high-resolution laboratory studies in the far-infrared and middle infrared regions have produced major improvements in the line parameters for the pure rotation and the most important infrared bands of normal ozone and its 1SO-substituted isotopic varieties. These parameters have been used to identify and quantify 160180160 and 16016OJ80 features in ground-based infrared solar absorption spectra [Rinsland et al, 1985] [Kaye and Strobel, 1983;Kaye, 1986] predict negligibly small isotopic enhancement, it appears that the processes involved are not fully understood [Bates, 1988]. Some of these studies indicate that the enhancement should be in the 1601601•O.…”
Section: Introductionmentioning
confidence: 99%